Interpersonal cognition (Guilford Press, 2005)
"This volume presents state-of-the-art research on the processes by which people understand their interpersonal experiences. Leading investigators integrate findings from experimental social psychology with insights from developmental, personality, and clinical psychology, bringing fresh ideas to bear on universal issues and identifying salient directions for future research." "Interpersonal cognition is increasingly recognized as a central topic in social cognition, and this book brings together the most important current perspectives in the field. It will be read with interest by psychologists involved in the study of close relationships, and will serve as a text in graduate-level courses."--BOOK JACKET.